Development Synergy and Optimization of Growth Conditions of Chlorpyrifos Degrading Bacteria Consortium - Anzazi Haro, Lydia; Mwamburi Mjomba, Fredrick; Mwagandi Chimbevo, Lenny; Kamau Gicharu, Gibson; Juma Tom, Felix; Gona Makenzi, Nzaro (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Chlorpyrifos (CPF) [O, O-diethyl O-(3, 5, 6-trichloro-2-pyridyl) phosphorothioate)] is an organophosphorous used as a house hold and agricultural pesticide in various formulations has adverse toxic effects on human health which has created an environmental concern. In the recent years, degradation studies of chlorpyrifos have greatly increased but only a few biodegradations by consortia have been reported. This study aimed to develop bacteria consortia and optimizing their growth conditions of temperature and pH for effective biodegradation of chlorpyrifos. Experimental research design was used to determine optimum temperature and pH. Five consortia were assembled based on degradation ability. Group I consisted of all of the five bacteria isolates (Brachybacterium sp. (CP1), Exiguobacterium alkaliphilum (CP2), Advenella kashmirensis (CP3), Micrococcus luteus (CP5), Pseudomonas protegens (CP6) and Lysinibacillus sphaericus CP7). Group II was composed of high degraders (CP1, CP3 and CP5), Group III are moderate degraders (CP2, CP5 and CP6), Group IV low degraders (CP5, CP6 and CP7) and Group V, a mixture of low and high degraders (CP3, CP7 and CP6). Findings of this study showed that the optimal growth conditions of the bacteria isolates were pH and temperature of 7 and 25oC, respectively. Bacteria consortia had their optimal growth at a temperature of 25oC and 30oC, and pH range between 6 - 8. With Group I, III and IV with highest growth as indicated by high optical density. These results revealed the ability of these bacteria consortia (group I, III and VI) to be used in remediating chlorpyrifos contaminated environment. Further research is required to utilize these three consortia in a bioreactor in a way that is safe, affordable and environmentally friendly.